Smoking-attributable peptic ulcer disease mortality worldwide: trends from 1990 to 2021 and projections to 2046 based on the global burden of disease study - Li, Hao; Shi, Qi; Chen, Caiyun; Li, Ju; Wang, Kai (Frontiers in Public Health, 2024)
ObjectiveSmoking is a major risk factor for peptic ulcer disease (PUD) mortality. This study aims to analyze global trends in smoking-attributable PUD mortality from 1990 to 2021 and project future trends to 2046.MethodsData were obtained from the Global Burden of Disease Study 2021. We calculated age-standardized mortality rates (ASMR) and estimated annual percentage changes (EAPC) for smoking-attributable PUD mortality. Bayesian Age-Period-Cohort models were used to project future trends.ResultsFrom 1990 to 2021, global smoking-attributable PUD deaths decreased from 48,900 to 29,400, with the ASMR declining from 1.2 to 0.3 per 100,000 (EAPC: −4.25%). High-income regions showed faster declines, while some low- and middle-income countries experienced slower progress or even increases. Projections suggest a continued global decline in smoking-attributable PUD mortality to 2046, with persistent regional disparities. By 2046, the global ASMR is expected to decrease to approximately 0.1 per 100,000, with higher rates persisting in certain regions such as the Solomon Islands (3.7 per 100,000) and Cambodia (1.6 per 100,000).ConclusionWhile global smoking-attributable PUD mortality has significantly decreased and is projected to continue declining, substantial regional disparities persist. These findings underscore the need for targeted tobacco control interventions, particularly in high-risk regions, to further reduce the global burden of smoking-attributable PUD mortality.